Calcium bursts allow rapid reorganization of EFhD2/Swip-1 cross-linked actin networks in epithelial wound closure - Franziska Lehne; Thomas Pokrant; Sabnam Parbin; Gabriela Salinas; Jörg Großhans; Katja Rust; Jan Faix; Sven Bogdan (Nature Communications, 2022)
Calcium serves as an important second messenger in signal transduction to the actin cytoskeleton. Here, we identify EFhD2/Swip-1 as a calcium-dependent actin cross-linker promoting rapid reorganization of actin networks in epithelial wound closure.